Answer:
A
Step-by-step explanation:
Im not sure if its correct tho dont quote me on it ;(
Equation 1 is
,
Equation 2 is [/tex] 3x-2y = -1 [/tex]
for first equation LCD= 3 *5 = 15 , So we multiply whole equation by 15
![\frac{4}{3} *15x -\frac{2}{5}*15 y =2*15](https://tex.z-dn.net/?f=%20%5Cfrac%7B4%7D%7B3%7D%20%2A15x%20-%5Cfrac%7B2%7D%7B5%7D%2A15%20y%20%3D2%2A15%20)
![20x - 6y = 30](https://tex.z-dn.net/?f=%2020x%20-%206y%20%3D%2030%20)
Now multiply second equation by -3 , to make the coefficient of y equal and opposite , so that we can apply the elimination method
![-9x+6y = 3](https://tex.z-dn.net/?f=%20-9x%2B6y%20%3D%203%20)
Add both the equations
![20x -9x -6y +6y = 30+3](https://tex.z-dn.net/?f=%2020x%20-9x%20-6y%20%2B6y%20%3D%2030%2B3%20)
![11x= 33](https://tex.z-dn.net/?f=%2011x%3D%2033%20)
Divide both sides by 11
![x=3](https://tex.z-dn.net/?f=%20x%3D3%20)
Plug in any one of the equation we get
3(3) -2y = -1
9 - 2y = -1
subtract 9 from both sides
-2y = -10
divide both sides by -2
y=5
So the solution is x= 3 , y= 5
Which means
a. The system is consistent and independent. TRUE
Answer:
Each shows two lines that make up a system of equations. If the graphs of the equations intersect, then there is one solution that is true for both equations. If the graphs of the equations do not intersect (for example, if they are parallel), then there are no solutions that are true for both equations.
(f+g) (n) = (–5n +1 ) + (- 6n +2) = –11n +3
(f+g) (n) = –11n +3
(f+g) (–2) = – 11 (–2) +3 = 22 +3 = 25
I hope I helped you^_^